Legal Protection of Batik Based on Communal Rights in the Context of Digitalization and Globalization: A Reconstruction of Legal Policy - Anthon Fathanudien; Bias Lintang Dialog; Iman Jalaludin Rifa’i (Law Development Journal, 2026)
Batik, as a traditional cultural expression of Indonesia, embodies significant philosophical, cultural, and economic values; however, in the context of digitalization and globalization, its existence faces increasing threats of misappropriation, unauthorized commercialization, and weakening of communal rights. This study aims to analyze the legal protection of batik based on communal intellectual property and to reconstruct legal policy to achieve a more effective and equitable protection system. The research employs a normative juridical approach with a doctrinal legal research design, utilizing statute, conceptual, and comparative approaches. Data are derived from secondary legal materials, including legislation, legal doctrines, and scholarly works, and are analyzed through qualitative juridical methods to identify regulatory gaps and structural weaknesses. The findings reveal that although batik has been formally recognized under the communal intellectual property regime, such recognition remains largely administrative and has not been supported by strong enforcement mechanisms, particularly in responding to challenges arising from digital technology and global market dynamics. Furthermore, the absence of adaptive regulations, limited institutional coordination, and minimal community participation exacerbate the vulnerability of batik protection. The novelty of this research lies in proposing a reconstruction of legal policy that integrates political law perspectives with digital governance, emphasizing the strengthening of communal rights, regulatory adaptation, and equitable benefit-sharing mechanisms. This reconstruction is expected to transform legal protection from symbolic recognition into a responsive, just, and sustainable system in safeguarding batik as Indonesia’s cultural heritage.